PENETAPAN KADAR FENOLIK TOTAL EKSTRAK ETANOL 70% DAN FRAKSI ETIL ASETAT DAUN BAWANG DAYAK (Eleutherine palmifolia (L.) Merr) DENGAN METODE SPEKTROFOMETRI UV-VIS - Eka Kumalasari; Nazulla Mudjib Nararia; Siska Musiam (Jurnal Insan Farmasi Indonesia, 2021)
Dayak onion (Eleutherine palmifolia (L.) Merr). Is used by the people in Central Kalimantan as a traditional treatment by utilizing onion dayak tubers while the leaves are rarely used, the part of dayak onion leaves also have the potential to naturally be useful as traditional medicine because they contain compounds phenol. Phenol compounds are useful as antioxidants, anti-inflammatory, hemostatic and antitumor. The purpose of this study was to determine the content of phenolic chemical compounds in ethyl acetate fraction and 70% ethanol extract of dayak onion leaves and find out the total phenolic content contained. The sample in this study is Dayak onion leaves from Palangkaraya, Central Kalimantan. Extraction of onion dayak leaves using maceration method. Fraction extract was made by liquid-liquid extraction method with ethyl acetate solvent. The level determination method used was Uv-Vis Spectrophotometry with Folin ciocalteau reagent. The results of this study indicate that from 70% ethanol extract and dayak onion leaves ethyl acetate fraction is containing phenolic compounds. Phenolic levels in this study obtained total levels of dayak onion leaves ethyl acetate fraction was 10.61% ± 0.0019 said to be greater than the 70% ethanol extract content of dayak onion leaves was 2.23% ± 0.0002.